The concept of tax in the jurisprudence of the Colombian Constitutional Court - Romero Molina, Cesar Augusto; Bernal Sánchez, Laura Victoria; Soto Contreras, Eleazar (DIXI, 2013)
This research focuses in studying whether there actually is a concept of tax in Colombia, since the current laws do not employ adequate techniques to give positive norms coherence so that they maintain a certain harmony to constitutionally define taxes. Jurisprudence thus defines and gives an interpretation of this concept that is consistent within our legal framework, since law has defined the concept of tax by means of inconsistent expressions and with many voids, or when the use of said expressions is fragile within the text of the law.